Analysis of microbial diversity and resistant genes among three types of pork via metagenomic and HPC-NGS - Yu Zhang; Jiaxin Song; Junfei Zhou; Yingmin Jia; Aijin Ma (Food and Agricultural Immunology)
The aim of this study was to reveal whether different types of pork have distinct microbial contamination and resistance genes. This work employed metagenomics to investigate microbial contamination in organic, intensive, and cage-free pork. HPC-NGS allowed for the detection of resistance gene content and distribution. Compared to organic and cage-free pork, the microorganisms in intensive pork were noticeably richer and more diverse. 18 resistance genes with a relative content of 122.12 were found in intensive pork; 11 resistance genes with a relative content of 5.07 were found in organic pork; 7 resistance genes with a relative content of 7.97 were found in cage-free pork. The kinds and contents of antibiotic-resistant genes in intensive pork were significantly higher than those in organic and cage-free pork. In conclusion, under feeding conditions with minimal antibiotics, pork will have comparatively low levels of antibiotics-resistance genes and bacteria of all kinds.